ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN AIR BERSIH UNTUK MEMENUHI KEBUTUHAN PELAYANAN AIR BERSIH DI PT. AIR MINUM INTAN BANJAR - Bisma, Bayu Cipta Setia; Lilimantik, Emmy; Fauzana, Noor Arida; Aziz, Yusuf (EnviroScienteae, 2024)
The Regional Government of Banjar Regency and Banjarbaru City through PT. Air Minum Intan Banjar is responsible for the production and marketing of clean water. Government through PT. Air Minum Intan Banjar Water certainly continues to strive to meet the needs of the community for clean water through the provision of clean water. Especially in Branch 2 Services of PT. Air Minum Intan Banjar As a buffer area for the capital city of Banjarmasin The need for clean water is a very vital factor in daily life and the increasing demand of the community, which is reflected by the increasing number of customers of PT. Air Minum Intan Banjar. The research was conducted in Banjar Regency with the number of samples taken as many as 100 (one hundred) respondents in the service area of Branch 2 PT. Air Minum Intan Banjar, which is spread across 7 sub-districts, namely Kertak Hanyar, Sei Tabuk, Tatah Makmur, Aluh-Aluh, Beruntung Baru, Martapura Barat and Gambut, was conducted with a Questionnaire Survey of PT. Air Minum Intan Banjar is selected by proportional stratified random sampling according to location and customer qualification. The dependent variable used in this study is water demand (Y), while the independent variable used in this study is the number of occupants (X1), the amount of income (X2), the type of tariff (X3), customers (X4). Data processing techniques using SPSS applications, using multiple regression analysis of factors affecting clean water demand in Banjar Regency. The results showed that the variables were the number of occupants (X1), the amount of income (X2), and. Type of tariff ( X4) has a positive effect on the consumption of clean water PT. Air Minum Intan Banjar (Y), while the number of customers (X3) negative effects. The community's clean water needs in 2023 at PT. Air Minum Intan Banjar Branch 2 area to serve 7 sub-districts in 2032 is 563,02  liters / second. This study recommends that there is a need for additional production capacity of PT. Intan Banjar Drinking Water so that for areas that have not been served for 24 hours, there needs to be an increase in clean water supply.